Modeling Patterns of Total Dissolved Solids Release from Central Appalachia, USA, Mine Spoils. Issue 1 (1st January 2017) - Clark, Elyse V.; Zipper, Carl E.; Daniels, W. Lee; Orndorff, Zenah W.; Keefe, Matthew J.
Abstract : Surface mining in the central Appalachian coalfields (USA) influences water quality because the interaction of infiltrated waters and O2 with freshly exposed mine spoils releases elevated levels of total dissolved solids (TDS) to streams. Modeling and predicting the short‐ and long‐term TDS release potentials of mine spoils can aid in the management of current and future mining‐influenced watersheds and landscapes. In this study, the specific conductance (SC, a proxy variable for TDS) patterns of 39 mine spoils during a sequence of 40 leaching events were modeled using a five‐parameter nonlinear regression. Estimated parameter values were compared to six rapid spoil assessment techniques (RSATs) to assess predictive relationships between model parameters and RSATs. Spoil leachates reached maximum values, 1108 ± 161 μS cm −1 on average, within the first three leaching events, then declined exponentially to a breakpoint at the 16th leaching event on average. After the breakpoint, SC release remained linear, with most spoil samples exhibiting declines in SC release with successive leaching events. The SC asymptote averaged 276 ± 25 μS cm −1 . Only three samples had SCs >500 μS cm −1 at the end of the 40 leaching events. Model parameters varied with mine spoil rock and weathering type, and RSATs were predictive of four model parameters. Unweathered samples released higher SCs throughout the leaching period relative to weathered samples, and rock type influenced the rate of SC release. The RSATs for SC, total S, and neutralization potential may best predict certain phases of mine spoil TDS release. Core Ideas: Appalachian mine spoil specific conductance leaching patterns were modeled. Weathering type influenced specific conductance at the beginning and end of the leaching period. Rock type influenced rates of specific conductance release. Considering all mine spoils, RSATs predicted four model parameters.